2016
DOI: 10.1159/000452594
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Vascular Resistance is Associated With a Prothrombotic State in Hypertensive Patients

Abstract: Background/Aims: Hypertensive nephroangiosclerosis is associated with progressive increase of intrarenal vascular resistance. In addition to blood pressure, other factors can contribute to hypertensive renal damage including a prothrombotic state. We investigated the relationship between hemostatic markers and intrarenal vascular resistance in hypertension. Methods: In 115 untreated, nondiabetic, hypertensive subjects free of cardiovascular complications and advanced renal function impairment, we measured 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Therefore, an investigation of changes in PTS might have both practical significance and clinical value. A previous study found that a combined increase in fibrinogen and D‐dimer levels might indicate the existence of PTS. Because blood viscosity was found to be significantly increased in a group of patients with small artery occlusion, and ADP‐induced platelet aggregation function is a predictive factor of poor coronary events, these indices were included among the present items for comprehensive screening of PTS.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, an investigation of changes in PTS might have both practical significance and clinical value. A previous study found that a combined increase in fibrinogen and D‐dimer levels might indicate the existence of PTS. Because blood viscosity was found to be significantly increased in a group of patients with small artery occlusion, and ADP‐induced platelet aggregation function is a predictive factor of poor coronary events, these indices were included among the present items for comprehensive screening of PTS.…”
Section: Discussionmentioning
confidence: 96%
“…In several studies, increased intrarenal RI is directly correlated to cardiovascular risk, systemic atherosclerosis, and mortality. For example, in essential hypertensive patients with GFR higher than 30 mL/min/1.73 m 2 , Catena et al showed that intrarenal RI is associated with a pro-thrombotic state [ 30 ], while Pontremoli et al observed an independent correlation between intrarenal RI, carotid intima-media thickness, and left ventricular hypertrophy [ 15 ]. In addition, Watanabe et al observed that intrarenal RI is associated with multi-site atherosclerosis assessed by the coronary artery calcium score and the carotid intima-media thickness in patients with preserved renal function and these associations are independent of hypertension [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the cause of resistant hypertension, all patients seen at the clinic are routinely screened with clinical and laboratory testing that include analysis of medical records and adherence to treatment, physical examination, urine analysis, blood biochemistries, duplicate measurements of 24-hour creatinine clearance and urinary sodium excretion, plasma active renin and aldosterone, urinary cortisol and catecholamines, electrocardiogram, echocardiography, polysomnography, renal ultrasound with duplex Doppler examination of intrarenal vessels, and renal angio-CT scan or angio-MRI [14]. Renal angiography was performed in all patients in whom increased intrarenal duplex systolic velocity was detected and/or renal artery stenosis was demonstrated either at angio-MRI or angio-CT scan [15]. Patients were classified as smokers if they had smoked for at least 5 years, and up to 1 year before the study.…”
Section: Methodsmentioning
confidence: 99%